From the deep woods to civilization : chapters in the autobiography of an Indian - Eastman, Charles A., 1858-1939 (North American Indian thought and culture., 1916)
From deep woods to civilization continues Eastman's captivating autobiographical work after Indian boyhood, telling the story of his years during school and into his life as a doctor. One of the highest educated Indians of his time, through his social work and his writings he was one of the best-known Indians of the early 20th century.